Trends and hotspots in landscape transformation based on anthropogenic impacts on soil in Hungary, 1990–2018 - Balogh, Szabolcs; Novák, Tibor József (Hungarian Geographical Bulletin, 2020)
The transformation of the landscapes due to the anthropogenic activities is increasing worldwide. These changes are also manifested in the change of soil-forming processes. The land cover (LC) changes evaluated according to their influence on anthropogenic features of soils allows to distinguish between LC changes resulting increased and decreased human impact (HI). In our study, we assess the changes of HI on landscapes and its spatial distribution across Hungary. The changes were evaluated by using LC data of four periods between 1990 and 2018 reclassified based on the related anthropogenic soil features. To identify the hotspots of the changes 1×1 grids were applied in which the direction (increasing, neutral or decreasing HI) and frequency (number of landscape patches with LC changes) of changes were evaluated. In our research, the hotspots were identified over the studied four periods. We point out that the spatial distribution of hotspots is very different. The hotspots of the increased human impact are 2,449 cells (643.0 km2 ) between 1990 and 2018, and the most of it localized in the Pest Plain (67), Csepel Plain (64) and Nagykálló-Nyírség (60). Most of the multiple hotspots are in the outskirts of Budapest to Kiskunlacháza, Bugyi, Délegyháza. As we examine the decreasing hotspot data we found 1,679 cells (1,524.9 km2 ) between 1990 and 2018. In largest number, they occur on the Kiskunság Sand Ridge (38), Majsa–Szabadka Sand Ridge (37) and Nagykállói-Nyírség (36). Multiple hotspots are located in settlements Izsák, Ásotthalom, Vatta and Nyírmihályi. Regions with numerous hotspots require special management to moderate its negative consequences on soils to consider both increased anthropisation, but also extensification of land use and their consequences.